Big data analytics for entrepreneurial success - Sedkaoui, Soraya (Business Science Reference, 2019)
"This book addresses the issue of big data analytics from a practical angle for entrepreneurs with a pedagogical explanation of the operation of its main methods and concrete demonstrations of their use. It also builds a common set of concepts, terms, references, methods, applications and approaches in this area"--